Green marketing today – a mix of trust, consumer participation and life cycle thinking - Lewandowska Anna; Witczak Joanna; Kurczewski Przemysław (Management)
A transition for a green, circular economy has encouraged companies to use new tools which boost sustainability. The purpose of this article is to discuss the consideration of life cycle thinking in green marketing as realized by companies. This theoretical-conceptual study aims to analyze life cycle assessment (LCA) as a useful tool for assessing green marketing goals. We also intend to highlight the importance of creating consumer trust for green business by displaying the green credentials of the products and activities. The article presents t he virtues and shortcomings of the LCA results relative to marketing management. As a result, the literature presents some gaps in terms of addressing life cycle thinking in marketing management and linking with consumer participation and trust.